السلم المتوازي وتطبيقاته المعاصرة: دراسة فقهية تقويمية: Parallel Salam and Its Contemporary Applications: A Jurisprudential Evaluation Study - الدكتور محمد بليه حمد العجمي (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
البحث بعنوان " السلم المتوازي وتطبيقاته المعاصرة "، وقد تناولتها في مقدمة وستة مطالب وخاتمة. أما المقدمة فتناولت فيها أهداف البحث ومشكلة البحث والدراسات السابقة للموضوع ومنهجية كتابة البحث وهو المنهج التحليلي، حيث أقوم بتحليل موقف الفقهاء المعاصرين وأقوالهم وأدلتهم في القضية تمهيدا لبيان الراجح منها وموقف المجمع في تلك القضية والأصل الذي اعتمد عليه، وأتخذ في طريقة في الكتابة منهجا موحدا كما هو متبع في البحوث العلمية المقارنة. وأما المطلب الأول فعرفت فيه السلم المتوازي مع ذكر عناصره, والمطلب الثاني ذكرت فيه الفرق بين السلم المتوازي والسلم العادي, وأما المطلب الثالث فخصصته لبيان حكم السلم المتوازي في الفقه الاسلامي, وأما المطلب الرابع فتحدثت فيه عن تطبيقات للسلم المتوازي, وأما المطلب الخامس فأورت فيه قرار مجمع الفقه الإسلامي بشأن السلم المتوازي, وأما المطلب السادس فبينت فيه الأصول التي استند عليها المجمع في فتواه بخصوص السلم المتوازي, ثم بعد ذلك الخاتمة فقد ضمنتها أهم النتائج المستخلصة من البحث, ثم ختمت البحث بالمراجع والمصادر. Abstract The research titled "Parallel Salam and its Contemporary Applications" has been dealt with an introduction, six topics and a conclusion. As for the introduction, I dealt with the objectives of the research, the research problem, previous studies of the subject, and the methodology of writing the research, which is the analytical approach. Whereas I analyze the position of contemporary jurists, their sayings and evidence in the case in preparation for the statement of the most correct of them, and the position of the Council in that case, and the principle on which it was relied. In writing, I took a unified approach as in the case of another same scientific research. As for the first topic, I defined the Parallel Salam and mentioned its elements, and in the second topic I mentioned the difference between Parallel Salam and ordinary Salam, and as for the third topic, I devoted it to explain the rule of Parallel Salam in Islamic jurisprudence, and as for the fourth topic, I talked about applications of Parallel Salam. For the fifth topic, I explained the decision of the Islamic Fiqh Academy regarding Parallel Salam, and as for the sixth topic, I clarified the principles on which the Council relied in its fatwa regarding Parallel Salam, then after that, I included in the conclusion the most important results extracted from the research, then concluded the research with references and sources. Keywords: Parallel Salam, Islamic Jurisprudence, Islamic Fiqh Academy